Some Observations on the Houses of the Prophet Muhammad (pbuh) and the First Muslims in Madinah - Spahic, Omer (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Some Observations on the Houses of the Prophet Muhammad (pbuh) and the First Muslims in Madinah